Impact of cryopreservation protocols (one- and two-step) on boar semen quality at 5 °C and post-thawing - Monteiro, Matheus Saliba; Torres, Mariana Andrade; Passarelli, Marina da Silva; Martins, Matheus Passini; Ravagnani, Gisele Mouro; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antônio [UNESP]; Dell'Aqua Júnior, José Antônio [UNESP]; Yasui, George Shigueki; Martins, Simone Maria Massami Kitamura; de Andrade, André Furugen Cesar (Elsevier, 2022)
The two-step protocol (2 S) is currently used for boar semen cryopreservation. In this method, the cryoprotectant penetrant agents (CPAs) are added at 5 °C to reduce the toxicity of CPAs. An alternative is the one-step protocol (1 S), which is easier, cheaper, and reduces the necessity of equipment, but could increase the toxicity of CPAs. Currently, there are no studies that compared both protocols for boar semen cryopreservation. This experiment aimed to study the effect of cryopreservation protocol (1 S vs 2 S) on boar spermatozoa. In the one-step protocol, after centrifugation, the spermatozoa pellet was resuspended at 17 °C in the extender containing CPAs to achieve a concentration of 1 × 109 spermatozoa/mL and then submitted to cryopreservation. For the two-step protocol, the sperm pellet was resuspended in fraction A at 17 °C to achieve a concentration of 1.5 × 109 spermatozoa/ mL, and then allowed to cool to 5º C before fraction B with CPA was added to the sample to achieve a final concentration of 1 × 109 spermatozoa/mL and followed by freezing. The cryopreservation protocol did not impact total motility at 5 °C (1 S: 78.5 % vs 2 S: 79 %, p > 0.05). After thawing, the two-step protocol improved (p < 0.05) total (1 S: 18.2 % vs 2 S: 29.5 %) and progressive motility (1 S: 9 % vs 2 S: 15%). Further, the 2 S protocol increased (p < 0.05) the percentage of rapid spermatozoa (1 S: 8.7 % vs 2 S: 14.6 %) and spermatozoa with intact plasma and acrosomal membrane (IAIP) (1 S: 40.5 % vs 2 S: 61.5 %), and increased (p < 0.05) live sperm cells with high mitochondrial potential (MHIP) (1 S: 42.9 % vs 2 S: 60 %). The boar semen cryopreservation method (TRT) did not (p > 0.05) alter membrane lipid disorder, lipid peroxidation, and superoxide anion. Thus, the best method for boar semen cryopreservation is the two-step protocol.
Keywords: Boar sperm; Cryopreservation; Flow cytometer; Glycerol; Swine; Two-steps